2020
DOI: 10.1186/s40729-020-00235-5
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement in molar extraction sockets: a systematic review and meta-analysis

Abstract: Background: Immediate implants are frequently employed in the anterior maxillary area. However, the installation of dental implants simultaneously with tooth extraction can also provide with benefits in the posterior areas with a reduction in time prior the recovery of the masticatory function. Results previously reported in the literature show high-survival and success rates for implants placed in extraction sockets in molar areas; however, this topic has received limited systematic analysis. Material and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 30 publications
2
55
0
6
Order By: Relevance
“…Unlike studies on drilling in healed alveolar ridges, many studies on implant placement in extraction sockets have focused on single-rooted teeth such as premolars and those found in the esthetic zone [10][11][12] . However, in recent years, many studies on IIP in fresh extraction sockets of molars have been performed [13][14][15] .…”
Section: Position Of Implant Fixture Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike studies on drilling in healed alveolar ridges, many studies on implant placement in extraction sockets have focused on single-rooted teeth such as premolars and those found in the esthetic zone [10][11][12] . However, in recent years, many studies on IIP in fresh extraction sockets of molars have been performed [13][14][15] .…”
Section: Position Of Implant Fixture Placementmentioning
confidence: 99%
“…Bone grafting at the gap is recommended to improve bone contact to the implant surface and decrease gingival recession resulting from horizontal bone resorption 22 - 24 . Although, there is not enough evidence supporting the need for augmentation at the gaps and the kinds of augmentation procedures 25 , many studies have shown that bone grafting improves implant survival and success rates 15 .…”
Section: Bone Augmentationmentioning
confidence: 99%
“…Replacement of a hopeless molar with a dental implant is one of the most frequent therapeutic modalities in implant dentistry 1 and this tooth replacement modality has shown predictable long‐term outcomes with high survival rates and successful results 2,3 . Because of the increased interest in shortening the overall treatment time and in order to reduce the invasiveness of surgical interventions, 4 immediate implant placement (Type 1) was proposed by several authors and different surgical protocols have been explored 5‐7 . Although immediate implant placement in molar areas has shown high survival rates of 96.6% 7 clinical data from literature remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increased interest in shortening the overall treatment time and in order to reduce the invasiveness of surgical interventions, 4 immediate implant placement (Type 1) was proposed by several authors and different surgical protocols have been explored 5‐7 . Although immediate implant placement in molar areas has shown high survival rates of 96.6% 7 clinical data from literature remains limited. To add to that, immediate implant placement does not counteract the post extraction bone resorption as widely described in the literature 8‐12 while alveolar ridge preservation (ARP) techniques with the use of space filling biomaterials have proven to significantly limit bone remodeling after extraction and preserve, at least partially, the contour of the alveolar ridge 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The immediate loading after tooth extraction was introduced in 1976 as an alternative to the classic delayed implant placement described by Branemark [ 2 ], and it is widely described in literature [ 3 , 4 ]. This procedure seems to preserve the integrity of the socket itself [ 5 ], providing favorable results with outcomes similar to implants placed in healed edentulous ridge [ 6 ].…”
Section: Introductionmentioning
confidence: 99%